Application of vibrational spectroscopy techniques to non-destructively monitor plant health and development1. Issue 10 (21st May 2015) - Butler, Holly J.; McAinsh, Martin R.; Adams, Steven; Martin, Francis L.
<x xml:space="preserve">Abstract</x> Characterisation of plant leaf growth employing vibrational spectroscopy approaches.